The Interface Between Practice and Theory Within Participation and Decision Making: The Development of a Precinct Plan in the Suburb of Bramley, Johannesburg - Lishivha, Keitumetse (University of the Witwatersrand, Johannesburg, 2015)
In essence the study will investigate the link between Governance and Development control and how fair and inclusive the processes of decision making are by looking at these processes in the formation of the Precinct Plan of a specific neighbourhood. At the end of this research process I outline what has been discovered through the research process and identify to what extent the participatory process within the Precinct Plan process has accounted for the different interests of different stakeholders. From that I deduce if and how the decision making process in precinct Plans needs to be changed to be more participatory or whether we need to find more pragmatic and contextually applicable participatory processes to ensure equal contribution in contested spaces. The main interest of this study investigates how different interests of stakeholders are managed .The study attempts to uncover the rationale behind changes in land use and the prioritisation of land use in that specific space and how these decisions are particularity influenced by interest-based negotiations.
Planning Honours Report 2015, Wits University
Keywords: governance, development control, precinct plan, land use, participation, decision making, process. contested spaces